A Mass Spectrometric Method for Use of Stable Isotopes as Tracers in Studies of Iron, Zinc, and Copper Absorption in Human Subjects - Johnson, Phyllis E. (The Journal of nutrition, 1982)
Stable isotopes of iron, zinc, and copper can be used singly and in combination as tracers of mineral metabolism in human subjects. A mass spectrometric method of analysis that uses chelation of these metals with tetraphenylporphyrin was developed. Absorption can be determined by measuring isotope appearance in feces after a single pulse dose. The method is satisfactory for 54Fe, 67Zn, and 65Cu. Detection of 57Fe and 70Zn in feces is not very reliable. stable isotopes iron zinc copper metal absorption mass spectrometry